2019
DOI: 10.5117/tvt2019.3.002.sang
|View full text |Cite
|
Sign up to set email alerts
|

Effecten van narrativiteit in educatieve teksten

Abstract: This study aims to gain more insight into narrativity in the educational domain. Based on earlier research, we define three prototypical narrative elements (i.e., the presence of particularized events, an experiencing character, and a landscape of consciousness), and present an analytic model that illustrates how varying combinations of these elements occur in Dutch educational materials for Social Studies and Science. Using this model, we then analyze experimental texts from previous studies on the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous experimental research has shown conflicting results in this respect (see also Section 1). However, since these studies have used different operationalizations of the notions "expository" and "narrative", no firm conclusions can yet be drawn about the relative effectiveness of narrative versus expository educational texts (Sangers et al, 2019). Therefore, future research should pursue a more consistent approach to the manipulation of these genres in experimental texts.…”
Section: Narrative Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experimental research has shown conflicting results in this respect (see also Section 1). However, since these studies have used different operationalizations of the notions "expository" and "narrative", no firm conclusions can yet be drawn about the relative effectiveness of narrative versus expository educational texts (Sangers et al, 2019). Therefore, future research should pursue a more consistent approach to the manipulation of these genres in experimental texts.…”
Section: Narrative Elementsmentioning
confidence: 99%
“…These conflicting results are partly explained by the way in which narrativity has been operationalized in the experimental texts of these studies, as the number and kinds of narrative elements used in these studies vary considerably (cf. Sangers, Evers-Vermeul, Sanders & Hoeken, 2019). This suggests that the narrative genre has not yet been clearly defined within the boundaries of the educational domain.…”
Section: Introductionmentioning
confidence: 99%